Community reporting on violent extremism by "intimates": emergent findings from international evidence. Issue 4 (1st October 2020) - Thomas, Paul; Grossman, Michele; Christmann, Kris; Miah, Shamim
ABSTRACT: To promote early intervention strategies, Countering/Preventing Violent Extremism (C/PVE) policies internationally seek to encourage community reporting by "intimates" about someone close to them engaging in terrorist planning. Yet historically, we have scant evidence around what either helps or hinders "intimates" to share concerns with authorities. We address that deficit here through a "state of the art" assessment of what we currently know about effective related C/PVE approaches to community reporting, based on key findings from a ground-breaking Australian study and its UK replication. The consistency of qualitative findings from nearly 100 respondents offers new paradigms for policy and practice.